2011
DOI: 10.1038/jp.2011.166
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular instability after patent ductus arteriosus ligation in preterm infants: the role of hydrocortisone

Abstract: Objective: Following patent ductus arteriosus (PDA) ligation, preterm infants may develop profound hypotension and respiratory failure. Prophylactic stress hydrocortisone (HC) has emerged as a therapy to prevent complications, postulating these infants do not synthesize steroids because of an immature hypothalamic-pituitary-adrenal axis. The purpose of this study was to compare outcomes in infants who received stress HC before their PDA ligations to those who did not.Study Design: A retrospective chart review … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 18 publications
0
7
1
Order By: Relevance
“…In spite of lack of evidence, some centers routinely prescribe prophylactic hydrocortisone preoperatively. A recently published retrospective study of preterm infants undergoing ligation found no difference in postoperative outcomes between infants treated with and without prophylactic hydrocortisone preoperatively [18]. That study differs from ours as none of the infants were treated with milrinone or underwent ACTH stimulation testing.…”
Section: Discussioncontrasting
confidence: 52%
“…In spite of lack of evidence, some centers routinely prescribe prophylactic hydrocortisone preoperatively. A recently published retrospective study of preterm infants undergoing ligation found no difference in postoperative outcomes between infants treated with and without prophylactic hydrocortisone preoperatively [18]. That study differs from ours as none of the infants were treated with milrinone or underwent ACTH stimulation testing.…”
Section: Discussioncontrasting
confidence: 52%
“…[ 48 ]. Third, cardiovascular instability after patent ductus arteriosus ligation (i.e., post-ligation cardiac syndrome, PLCS) in preterm infants has been reported [ 49 ], as it has a tendency toward a higher risk of long-term neurodevelopmental impairment [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…7 The use of postoperative cortisol, however, may lead to delay in treatment, random serum cortisol levels do not predict PLCS 28 and prophylactic stress dose hydrocortisone for all infants is not associated with improved outcomes. 29 Preoperative serum cortisol following adrenocorticotropic hormone (ACTH) stimulation of less than 750 nmol/L, however, has been associated with PLCS 26 and preoperative assessment of adrenal performance may facilitate early administration to appropriately selected patients. Stress dose hydrocortisone should be considered for infants already receiving preoperative steroids for lung disease or hypotension 29 as well as for symptomatic patients particularly in the setting of a failed ACTH stimulation test.…”
Section: Perioper Ative Op Timiz Ationmentioning
confidence: 99%
“…Developmental immaturity of the hypothalamic‐pituitary‐adrenal axis and adrenal hypoperfusion due to chronic ductal steal are potential contributors to early postoperative hypotension (0‐4 h) and poor response to catecholamine therapy is associated with low postoperative serum cortisol . The use of postoperative cortisol, however, may lead to delay in treatment, random serum cortisol levels do not predict PLCS and prophylactic stress dose hydrocortisone for all infants is not associated with improved outcomes . Preoperative serum cortisol following adrenocorticotropic hormone (ACTH) stimulation of less than 750 nmol/L, however, has been associated with PLCS and preoperative assessment of adrenal performance may facilitate early administration to appropriately selected patients.…”
Section: Perioperative Optimizationmentioning
confidence: 99%